Pendampingan Pendataan dan Pembaruan Harga Barang Kebutuhan Pokok untuk Meningkatkan Akurasi Data di Bidang Perdagangan dalam Negeri Dinas Perindustrian dan Perdagangan Provinsi Jawa Tengah - Mila Dea Anathasia; Muhammad Abdullah Mafahir; Ahmad Rohidin; Riyono Riyono (Lembaga Pengembangan Kinerja Dosen, 2025)
This service activity was carried out in the Domestic Trade Sector, Central Java Provincial Industry and Trade Office with the aim of supporting the data collection process and updating the prices of basic necessities. This activity focuses on providing accurate and up-to-date price data as the basis for making price stabilization policies by local governments. The implementation of activities includes observation of the internal data collection system, daily price data input, data validation, and preparation of price development reports. In addition, the service team also coordinates with field officers and market managers to ensure the completeness of information and consistency of the data received. The technical assistance process related to the use of data collection application tools is also carried out to improve the competence of apparatus in managing information more effectively. The results of the activity show that systematic data updates are able to improve administrative efficiency, database accuracy, and support decision-making processes related to regional economic stability. Furthermore, the availability of more reliable price data allows local governments to detect potential price fluctuations early and formulate more timely and targeted intervention steps.